Organization of DNA in a bacterial nucleoid. Issue 1 (December 2016) - Tolstorukov, Michael; Virnik, Konstantin; Zhurkin, Victor; Adhya, Sankar
Abstract Background It is unclear how DNA is packaged in a bacterial cell in the absence of nucleosomes. To investigate the initial level of DNA condensation in bacterial nucleoid we used in vivo DNA digestion coupled with high-throughput sequencing of the digestion-resistant fragments. To this end, we transformedE. coli cells with a plasmid expressing micrococcal nuclease. The nuclease expression was under the control of AraC repressor, which enabled us to perform an inducible digestion of bacterial nucleoid inside a living cell. Results Analysis of the genomic localization of the digestion-resistant fragments revealed their non-random distribution. The patterns observed in the distribution of the sequenced fragments indicate the presence of short DNA segments protected from the enzyme digestion, possibly because of interaction with DNA-binding proteins. The average length of such digestion-resistant segments is about 50 bp and the characteristic repeat in their distribution is about 90 bp. The gene starts are depleted of the digestion-resistant fragments, suggesting that these genomic regions are more exposed than genomic sequences on average. Sequence analysis of the digestion-resistant segments showed that while the GC-content of such sequences is close to the genome-wide value, they are depleted of A-tracts as compared to the bulk genomic DNA or to the randomized sequence of the same nucleotide composition. Conclusions Our results suggest that DNA is packaged in the bacterial nucleoid in a non-random way that facilitates interaction of the DNA binding factors with regulatory regions of the genome.